2003
DOI: 10.1002/jcb.10468
|View full text |Cite
|
Sign up to set email alerts
|

TE2 and TE1 sub‐elements of the testis‐specific histone H1t promoter are functionally different

Abstract: The testis-specific linker histone H1t gene is transcribed exclusively in pachytene primary spermatocytes. Tissue specific expression of the gene is mediated in part by transcriptional factors that bind elements located within the proximal and distal promoter. A 40 bp promoter element, designated H1t/TE, that is located within the proximal promoter between the CCAAT-box and AC-box, is known to be essential for H1t gene transcription in transgenic animals. In the present study, we show by SDS-PAGE analysis of U… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2003
2003
2008
2008

Publication Types

Select...
6
1

Relationship

4
3

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 45 publications
(79 reference statements)
0
6
0
Order By: Relevance
“…As a first step to test if the binding proteins detected by Clare et al [24] are related to the RFX family [25], we compared testis and liver NE by band-shift analysis, using labeled oligos containing either the H1t palindrome or the strong, interleukin-5 receptor ␣ (IL-5R␣) RFX site [34] ( Fig. 1, lanes 1-4).…”
Section: Identification Of the Nuclear Dna Binding Proteins For The Hmentioning
confidence: 99%
See 1 more Smart Citation
“…As a first step to test if the binding proteins detected by Clare et al [24] are related to the RFX family [25], we compared testis and liver NE by band-shift analysis, using labeled oligos containing either the H1t palindrome or the strong, interleukin-5 receptor ␣ (IL-5R␣) RFX site [34] ( Fig. 1, lanes 1-4).…”
Section: Identification Of the Nuclear Dna Binding Proteins For The Hmentioning
confidence: 99%
“…Clare et al [24] confirmed their observation but found that an additional set of complexes of similar mobilities was also formed from all somatic nuclear extracts. The identities of these bands have remained obscure, although Grimes recently suggested that the Te1 palindrome motif was related to the so-called X box in the promoters of the major histocompatibility complex II (MHCII) genes [25].…”
Section: Introductionmentioning
confidence: 99%
“…However, the GC-box overlaps TE1 and TE2, and it is not yet known if it is functional in activating transcription in spermatocytes in vivo. Mutations within TE1, TE2 or GC-box sub-elements leads to partial inactivation of the H1t promoter in transient expression assays (Wilkerson et al, 2002a;Wilkerson et al, 2003;Wolfe et al, 2004). Mutagenesis of any of these sites causes a decrease in reporter gene expression in the germinal derived GC-2spd cell line as well as in transfected nongerminal cells.…”
Section: H1t Promoter Elementsmentioning
confidence: 98%
“…2). The TE1 and TE2 subelements are imperfect inverted repeats, and TE1 serves as a binding site for a transcriptional activator (Grimes et al, 1992b;Grimes et al, 1992a;Wilkerson et al, 2002b;Wilkerson et al, 2002a;Wilkerson et al, 2003). The GC-box, located between TE1 and TE2, contribute to transcriptional activation in transient expression assays in some cell lines (Wilkerson et al, 2002b;Wilkerson et al, 2002a).…”
Section: H1t Promoter Elementsmentioning
confidence: 99%
“…Unlike other histone promoters, the H1t promoter contains an imperfect inverted repeat called the testis element (TE) shown to contain the two elements of the X‐box initially called TE1 and TE2, now called X‐box 1 and X‐box 2 [Grimes et al, 2003; Wilkerson et al, 2003]. Studies in transgenic mice showed that mutation of X‐box 1 and X‐box 2 in the rat H1t promoter abolished expression of the transgene [vanWert et al, 1998].…”
mentioning
confidence: 99%